An Evaluation on Planning Legislation Following the 1999 Earthquakes - Orhan, Ezgi (Kare Publ, 2022)
Following the 1999 Earthquakes stricken Marmara Region, as the most populated, urbanized and industrialized region of the country, large-scale recovery efforts have been initiated; and in addition to central and local administrations, many institutions and civil societies have become the part of these studies. However, in the face of the devastating effects of the 1999 Earthquakes, significant steps have been taken in legal framework due to its limitedness in guiding disaster policies. Besides, development of the risk management approach at the international level has triggered countries to review their policies and legal regulations shaping their disaster management. Based on this need, the study examines the legislation that shapes the disaster policies and guides spatial planning in our country and its change in the meantime. The legal regulations that have been added to the urban planning legislation in the last 20 years for the purpose of risk mitigation have been discussed. To this end, Article 73 of the "Municipality Law" (no. 5393), "Law on Conservation of Deteriorating Historic and Cultural Property through Renewal and Re-use" (no. 5366), "Law on the Transformation of Areas at Disaster Risk" (no. 6306), and Temporary Article 16 of Development Law (no. 3194) (Peace of Reconstruction) are determined as the main regulation shaping policies for reducing urban risks, and evaluated within the scope of the study. Therefore, this study puts forward the problems and criticisms regarding the implementation of legal arrangements established for the purpose of mitigating urban risks as well as recovery of the disaster-prone areas.
1999 Depremlerinin Ardından Planlama Mevzuatı Üzerine Bir Değerlendirme
Keywords: Disaster Planning; Disaster Risk Reduction; Planning Legislation; Kentsel Çalışmalar; İnşaat Mühendisliği; Kamu Yönetimi